2022
DOI: 10.3233/adr-220094
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Understanding of Hispanic Caregivers: Focus on Innovative Methods and Validations

Abstract: Alzheimer’s disease (AD) and Alzheimer’s disease-related disorders (ADRD) are late-onset, age-related progressive neurodegenerative disorders, characterized by memory loss and multiple cognitive impairments. Current research indicates that Hispanic Americans are at an increased risk for AD/ADRD and other chronic conditions such as diabetes, obesity, hypertension, and kidney disease, and given their rapid growth in numbers, this may contribute to a greater incidence of these disorders. This is particularly true… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 110 publications
0
10
0
Order By: Relevance
“…51 Informal caregivers within the Hispanic family system is extended, like our sample profile, persist in having the most unmet communication needs of any caregiver group and have significant unmet needs about understanding the disease, its process, and treatments. 52 Interventions are needed to promote caregiver engagement, communication activation, and inclusion in the patient care effort. 53 The brief online module described here, shown to improve communication knowledge and confidence encouraging caregiver communication activation, would provide dementia caregivers with an online resource accessed via computer or personal device.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…51 Informal caregivers within the Hispanic family system is extended, like our sample profile, persist in having the most unmet communication needs of any caregiver group and have significant unmet needs about understanding the disease, its process, and treatments. 52 Interventions are needed to promote caregiver engagement, communication activation, and inclusion in the patient care effort. 53 The brief online module described here, shown to improve communication knowledge and confidence encouraging caregiver communication activation, would provide dementia caregivers with an online resource accessed via computer or personal device.…”
Section: Discussionmentioning
confidence: 99%
“…51 Informal caregivers within the Hispanic family system is extended, like our sample profile, persist in having the most unmet communication needs of any caregiver group and have significant unmet needs about understanding the disease, its process, and treatments. 52 Interventions are needed to promote caregiver engagement, communication activation, and inclusion in the patient care effort. 53…”
Section: Discussionmentioning
confidence: 99%
“…In 2022, Hispanic or Latino minority residents were projected to exceed non-Hispanic white (NHWs) as the majority population in Texas [ 9 ]. According to the United States Census Bureau, NHWs are European Americans, North African Americans, and Middle Eastern Americans.…”
Section: Difference Between Hispanics and Non-hispanicsmentioning
confidence: 99%
“…Outside of the Alzheimer’s Association survey study, other research studies have found similar challenges among AA caregivers of AD/ADRD patients ( Table 4 ). Anyone who offers care to someone who requires additional assistance, such as individuals with AD and ADRD, is referred to as the caregiver [ 159 ]. Within any caregiver–patient relationship, there are five main elements of interactions that this relationship provides to AD/ADRD patients, which include: family traditions, emotional connections, family values, a helping network, and expectations of family roles [ 160 ].…”
Section: Risk Factors/susceptibility Of Ad In African Americansmentioning
confidence: 99%